2014
DOI: 10.9790/0837-19537281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Human Resource (HR) Practices on Nigerian Polytechnics Lecturers’ Performances

Abstract: Higher Education (HE) institutions in developing countries have become an area of attention to scholars in the field of Human Resource Management (HRM), particularly, African countries. Polytechnics are one of the higher education institutions (HEIs) in Nigeria, yet, they are not incorporated by scholars in their studies on HEIs, particularly, in Nigeria. This paper presents a study on how polytechnics lecturers perceive how certain Human Resource (HR) practices as recognized by Boselie et al (2005) found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition, Saleem and Khurshid (2014) conducted a study on the effect of recruitment and selection on job performance and found a strong positive connection between recruitment and selection and job performance. These findings are in line with Babagana's (2014) finding that indicates a positive relationship between recruitment and selection and job performance.…”
Section: Introductionsupporting
confidence: 92%
“…In addition, Saleem and Khurshid (2014) conducted a study on the effect of recruitment and selection on job performance and found a strong positive connection between recruitment and selection and job performance. These findings are in line with Babagana's (2014) finding that indicates a positive relationship between recruitment and selection and job performance.…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, there are several empirical studies conducted on the relationship between recruitment and selection and employee performance (e.g., Babagana, 2014;Saleem & Khurshid, 2014, so on). The overall findings of these studies signify significant positive relationship between recruitment and selection and employee performance.…”
Section: Linking the Selected Hr Practices To Employee Performancementioning
confidence: 99%
“…HRM and organizational psychology literature suggest the existence of extensive studies to explore the impact of employee participation on numerous constructs. For instance, employee participation and job satisfaction, employee commitment and employee productivity (Bhatti & Qureshi, 2007;Miller & Monge, 1986;Zhu, et al, 2015;Tafvelin, von Thiele Schwarz, Nielsen & Hasson, 2019;Basterretxea & Storey, 2018;Rogiest, Segers & van Witteloostuijn, 2018;Noe, Hollenbeck, Gerhart & Wright, 2017;Glavas, 2016), organizational performance (Summers & Hyman, 2005;Wang, Thornhill & Zhao, 2018), industrial democracy (Poole, 2017;Rasmussen, 2009), and PAs (Cawley, et al, 1998;Roberts, 2003;Thomas & Bretz Jr, 1994;Babagana, Mat & Ibrahim, 2019a & b;Rubin & Edwards, 2018;Islami, Mulolli & Mustafa, 2018;Babagana, Mat & Ibrahim, 2018;Rukumba & Iravo, 2019).…”
Section: Employee Participationmentioning
confidence: 99%
“…Moreover, performance appraisal (PA) is recognized as a critical component of an efficient human resource management (HRM) (Guest, 1997). According to Babagana (2014), HRM involves policies that are intended to boost employees' commitment. One of such HRM policies is employee performance appraisal which organizations in both the public and private sectors use to assess and manage employee performance (Khedkar, 2015).…”
Section: 10 Introductionmentioning
confidence: 99%